Integrasi Keterampilan 4C dan Nilai-Nilai Islam dalam Pembelajaran Abad ke-21 di Madrasah Ibtidaiyah - Sikana, Arina Mana; Fauzi, Imron; Zawawi, M. Ilmil (Program Studi PGMI, Universitas Al Falah As Sunniyah Kencong Jember, 2025)
This study aims to analyze the integration of 21st-century skills (4C: critical thinking, creativity, communication, and collaboration) with Islamic values in learning at Madrasah Ibtidaiyah. Using a descriptive qualitative approach and library research method, the study reviews relevant national and international literature from 2020-2025 related to 4C development and Islamic education. Data were analyzed through content and thematic analysis to identify key concepts, strategies, and challenges in applying 4C within Islamic schools. The findings reveal that learning models such as STEM, Project-Based Learning, Problem-Based Learning, and Quantum Learning effectively foster students’ critical thinking, creativity, collaboration, and communication. However, the integration of Islamic values such as amanah (trustworthiness), ta’awun (cooperation), ijtihad (creative effort), and tafakkur (reflection) remains underexplored. This study proposes a new conceptual framework, the 4C-Islamic Integration Model, combining 21st-century competencies with Qur’an-based values to promote holistic and character-based learning. Theoretically, it enriches the discourse of progressive Islamic education, while practically it offers guidance for teachers and policymakers to design creative, collaborative, and value-oriented learning in the digital era.